Original articleSecretory meningiomas: immunohistochemical pattern of lectin and ultrastructure of pseudopsammoma bodies - Taraszewska, Anna; Matyja, Ewa (Folia Neuropathologica, 2014)
Secretory meningioma is an infrequent histological subtype of benign, WHO grade I meningioma, that is characterized by focal epithelial and secretory transformation of meningothelial cells. The leading histopathological feature of neoplastic tissue is the presence of eosinophilic hyaline inclusions, defined as “pseudopsammoma bodies”. These inclusions are mostly intracytoplasmic, different in size and often multiple. They are stained with periodic acid-Schiff (PAS) and are immunopositive for epithelial and secretory markers. The aim of this study was to determine the pattern of lectin bindings and ultrastructural features of secretory meningiomas. The examination was performed on 8 cases of secretory meningiomas that occurred in women and were mostly associated with prominent peritumoural oedema. Histologically, the tumours exhibited numerous eosinophilic, PAS positive pseudopsammoma bodies. Immunohistochemical studies revealed a strong, ring-like cytokeratin expression around the pseudopsammoma bodies. The inclusions were CEA and EMA positive but negative for vimentin. The immunolabeling with four lectins (PNA, SBA, Con A and DBA) was studied. The majority of pseudopsammoma bodies and surrounding tumour cells were strongly labelled with PNA and SBA. Immunolabelling with Con A showed irregular staining with high intensity in small inclusions. Immunostaining with DBA was seldom positive in inclusions and negative in the tumour cell cytoplasm. Ultrastructure of pseudopsammoma bodies exhibited advanced heterogeneity. The size of inclusions and the content of intracytoplasmic lumina varied greatly. Some pseudopsammoma bodies seemed to be located extracellularly and lacked the obvious lumina. Our ultrastructural study and lectin binding pattern support the unique epithelial and secretory transformation of neoplastic cells connected with their altered glycosylation.